Graphene field-effect transistor using gated ferroelectric thin film. (December 2021) - Alam, Injamul; Sa, Kadambinee; Das, Sonali; Subramanyam, B.V.R.S.; Subudhi, Subhasri; Mandal, Manoranjan; Patra, Santosini; Samanta, Buddhadev; Sahu, Rashmi Rekha; Swain, Sujata; Mahapatra, Apurba; Kumar, Pawan; et al.
Abstract: A graphene-based ferroelectric field-effect transistor (GFE-FET) has been fabricated using few-layer graphene sheets (FLGS) as channel layer and barium titanate (BTO) as gate insulating layer. The FLGS and BTO were prepared by electrochemical and sol-gel methods respectively. The prepared materials have been characterized by XRD, SEM, UV–Vis, FTIR, and Raman spectroscopy. The performance of GFE-FET was assessed and obtained reasonably high field-effect mobility ∼4.2 × 10 4 cm 2 V– 1 S −1 with on/off ratio of about 10 3 . The obtained results of the fabricated GFE-FET ensure incredible opportunity for various applications mostly in the electronic industry as an alternative to semiconductors. Highlights: Few-layer graphene sheets (FLGS) and barium titanate (BTO) particles were well prepared by an electrochemical and a sol-gel method. Fabricate a graphene-based ferroelectric field-effect transistor (GFE-FET) using a sol-gel spin coating method, where FLGS and BTO act as a channel layer and gate insulating layer. The field-effect mobility of fabricated GFE-FET is approximate 4.2 × 10 4 cm 2 V– 1 S −1 with an on/off ratio of about 10 3 . The excellent results of the fabricated GFE-FET give an incredible opportunity in the electronic industry as an alternative to semiconductors.